Pola Asuh Orang Tua dalam Mendukung Kemampuan Komunikasi Oral Anak Tunarungu pada Satuan Pendidikan Khusus di Kota Serang - Azizah, Aisyah Nur; Abadi, Reza Febri; Asmiati, Neti (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2026)
Abstract: This qualitative multiple-case study examined how parenting practices relate to oral communication among deaf children in three special education settings in Serang City. Participants were three children aged 13-18 years, three hearing parents, and three teachers. Observations, interviews, documentation, and field notes were analyzed through within-case coding, cross-case comparison, and triangulation. Two families showed predominantly authoritative parenting, whereas one showed a permissive tendency. Children A and I demonstrated functional oral communication through speech supported by hearing aids, lip-reading, sign, or writing. Child F showed limited articulation and instruction comprehension alongside intellectual disability and discontinued hearing-aid use. Responsive guidance and consistent multimodal communication appeared supportive, although auditory access, cognition, intervention continuity, and school support also shaped outcomes. Family–school collaboration and individualized strategies are recommended. Abstrak: Penelitian kualitatif studi multikasus ini mengkaji keterkaitan pola asuh dengan komunikasi oral anak tunarungu pada tiga satuan pendidikan khusus di Kota Serang. Partisipan terdiri atas tiga anak berusia 13-18 tahun, tiga orang tua dengar, dan tiga guru. Data observasi, wawancara, dokumentasi, dan catatan lapangan dianalisis melalui pengodean dalam kasus, perbandingan lintas kasus, dan triangulasi. Dua keluarga menunjukkan kecenderungan pola asuh demokratis/otoritatif, sedangkan satu keluarga cenderung permisif. Anak A dan I memperlihatkan komunikasi oral fungsional melalui ujaran yang didukung alat bantu dengar, gerak bibir, isyarat, atau tulisan. Anak F memiliki keterbatasan artikulasi dan pemahaman instruksi disertai hambatan intelektual serta penghentian penggunaan alat bantu dengar. Bimbingan responsif dan komunikasi multimodal yang konsisten tampak mendukung, meskipun akses auditori, kondisi kognitif, kesinambungan intervensi, dan dukungan sekolah turut membentuk hasil. Kolaborasi keluarga–sekolah dan strategi individual direkomendasikan.